Ibn Rushd and his intellectual and philosophical role: A study of his intellectual influences in Europe and the Western opinion of him - Nemati, NourAlDin; Al-Azirjawi, Zainab Nasser AbdulHussein (Journal of Humanities & Social Sciences, 2025)
The research deals with Ibn Rushd and his intellectual and philosophical role as a historical study of his intellectual influence on Europe and to know the Western opinion about him. The research aims to clarify the role of Ibn Rushd’s philosophy and thought and their impact on the Western world by introducing Ibn Rushd and mentioning his most important ideas, then identifying how they spread and influenced Europeans. Therefore, the historical and descriptive method was followed, based on collecting scientific material and working to criticize and analyze it to reach the historical truth. The research was divided into an introduction in which we presented the importance of the research, the reason for choosing it, the methodology, the time and place framework, and three sections. The first section dealt with an overview of Ibn Rushd’s life from his birth, upbringing, and education. In the second section, the intellectual background of Ibn Rushd’s philosophy was mentioned, explaining his most important ideas. In the third section, we discussed Ibn Rushd’s influence on Western society and learned the church’s reactions to it. The research ends with a conclusion in which the most important results reached by the research were presented, the gist of which is that Ibn Rushd is one of the philosophers and thinkers whose thought had a clear influence that reflects his scientific and intellectual status, as Ibn Rushd’s philosophy constituted a revival of Greek philosophy. This made his thought popular among the European public, but it posed a threat to the authority of the Church, given its divergent views. This necessitated harsh measures against those who followed his philosophy.